PENGARUH DIGITAL MARKETING DAN BRAND EQUITY TERHADAP KEPUTUSAN PEMBELIAN PADA PRODUK HOBIKU - Fauziyyah, Nabila; Azmi Ajnin Nadiah; Widya Nurmala; Ramayani Yusuf (Universitas Haji Sumatera Utara, 2024)
The aim of this research is to find out whether there is a positive influence between digital marketing and brand equity on purchasing decisions for Hobiku products in Kab. Garut. The type of research used in this research is quantitative research with associative methods. The author uses quantitative research techniques, because the research carried out is related to statistical tools to process questionnaire results so that it can be seen whether or not there is an influence between Digital Marketing and Brand Equity on Purchasing Decisions.To measure how influential Digital Marketing and Brand Equity are on purchasing decisions for Hobiku.id products in Garut Regency, using a quantitative method based on data originating from secondary data sources with a large sample of 100 respondents obtained from previously existing thesis literature studies. Technical data analysis uses simple correlation and regression using SPSS data tools. Using research methods through a descriptive quantitative approach shows the results that digital marketing variables have a significant positive effect on purchasing decisions, and brand equity also has a significant positive effect on purchasing decisions. This research recommends adding and developing factors that influence consumer behavior to make more in-depth purchasing decisions and use different research methods.